RETRACTED : Pemberdayaan Audit Internal untuk Mendorong Penguatan Moderasi Beragama pada Perguruan Tinggi Keagamaan Islam Negeri - Shaleh Shaleh; Deni Indrawan; Zaki Sima Fashimado; Yan Suryo Sumirat (MANAZHIM, 2023)
This research is motivated by the inability of internal audit at PT-BLU to encourage the performance of strategic government programs implemented through universities. One of the government's priority programs run by PT-BLU is a program to strengthen religious moderation. This study aims to identify the models of internal control implemented at PT-BLU and their empowerment to encourage the performance of strengthening religious moderation in Higher Education. For this purpose, researchers empowered qualitative research methods by collecting data using observation, interview and documentation techniques. The data collected was then checked for validity using the triangulation technique and analyzed using the Miles and Huberman technique. The results of the study show that: (1) there are 2 (two) models of internal control that have been implemented at PT-BLU, namely: the partial-thematic internal audit model and the collaborative internal control model. (2) there is an audit model that is being developed, namely a risk-based internal-partial audit model, and an audit model that has the potential to be further studied and applied to PTKIN-BLU in the future, namely an integrative audit model; (3) the models of internal control that have been implemented by PTKIN BLU can be empowered to support and encourage the strengthening of religious moderation and other strategic programs.